A survey on the today's world problem of increasing obesity - Birgani, Nafiseh Bahadori; Motamedi, Pezhman; Kanaani, Leila (Progress in Nutrition, 2020)
Introduction: Obesity generally occurs when there is an imbalance between energy intake and energy expenditure. Various factors including genetic, age, sex, disproportionate intake of energy-dense foods, lack of exercise, eating disorders; depression, sleeping culture, and socioeconomic status could lead to obesity. On the one hand, while developing countries are deal with reducing malnutrition and hunger; they are also confronted with the more complex problems of obesity and overweigh. In recent years, the increasing rate of obesity in these countries was so that exceeds the number of people suffering from food shortages. Given the considerable prevalence of obesity, it is predicted that more than 2.3 billion people worldwide will be affected by obesity by 2015 (1). Respiratory failure, asthmatic attacks, gall stone, varicose veins, atherosclerosis, high blood pressure, high cholesterol, heart stroke, Reproductive Disorders and mental illness, are among the many complications of obesity (2, 20). Results: Given the importance of infant obesity in adult obesity, parental education is necessary for improving the diets of infants and avoiding urging to rapid weight gain in infants less than one year of age, since the urge to increase the volume of baby’s food can bring excessive weight gain and obesity in early childhood. On the other hand, drinking enough water is also helpful in preventing false appetite and obesity in children. Behavior and environment play a large role in overweight and obesity that are also the greatest areas for prevention and treatment actions. Add meals, from 3 to 5 servings, would cause increase the metabolism. The best method for fast slimming is to upturn the extended meals along with prolonged chewing. Conclusion: it can be stated that the best and most consistent way toward reducing weight to an ideal weight is achieved through appropriate life style, engage in physical activity and eat a healthy diet.